Development and clinical evaluation of an ionization chamber array with 3.5 mm pixel pitch for quality assurance in advanced radiotherapy techniques. Issue 5 (8th April 2016) - Togno, M.; Wilkens, J. J.; Menichelli, D.; Oechsner, M.; Perez‐Andujar, A.; Morin, O.
Abstract : Purpose: To characterize a new air vented ionization chamber technology, suitable to build detector arrays with small pixel pitch and independence of sensitivity on dose per pulse. Methods: The prototype under test is a linear array of air vented ionization chambers, consisting of 80 pixels with 3.5 mm pixel pitch distance and a sensitive volume of about 4 mm 3 . The detector has been characterized with 60 Co radiation and MV x rays from different linear accelerators (with flattened and unflattened beam qualities). Sensitivity dependence on dose per pulse has been evaluated under MV x rays by changing both the source to detector distance and the beam quality. Bias voltage has been varied in order to evaluate the charge collection efficiency in the most critical conditions. Relative dose profiles have been measured for both flattened and unflattened distributions with different field sizes. The reference detectors were a commercial array of ionization chambers and an amorphous silicon flat panel in direct conversion configuration. Profiles of dose distribution have been measured also with intensity modulated radiation therapy (IMRT), stereotactic radiosurgery (SRS), and volumetric modulated arc therapy (VMAT) patient plans. Comparison has been done with a commercial diode array and with Gafchromic EBT3 films. Results: Repeatability and stability under continuous gamma irradiation are within 0.3%, in spite of low active volume and sensitivity (∼200 pC/Gy). Deviation from linearity is in the range [0.3%, −0.9%] for a dose of at least 20 cGy, while a worsening of linearity is observed below 10 cGy. Charge collection efficiency with 2.67 mGy/pulse is higher than 99%, leading to a ±0.9% sensitivity change in the range 0.09–2.67 mGy/pulse (covering all flattened and unflattened beam qualities). Tissue to phantom ratios show an agreement within 0.6% with the reference detector up to 34 cm depth. For field sizes in the range 2 × 2 to 15 × 15 cm 2, the output factors are in agreement with a thimble chamber within 2%, while with 25 × 25 cm 2 field size, an underestimation of 4.0% was found. Agreement of field and penumbra width measurements with the flat panel is of the order of 1 mm down to 1 × 1 cm 2 field size. Flatness and symmetry values measured with the 1D array and the reference detectors are comparable, and differences are always smaller than 1%. Angular dependence of the detector, when compared to measurements taken with a cylindrical chamber in the same phantom, is as large as 16%. This includes inhomogeneity and asymmetry of the design, which during plan verification are accounted for by the treatment planning system (TPS). The detector is capable to reproduce the dose distributions of IMRT and VMAT plans with a maximum deviation from TPS of 3.0% in the target region. In the case of VMAT and SRS plans, an average (maximum) deviation of the order of 1% (4%) from films has been measured. Conclusions: The investigated technology appears to be useful both for Linac QA and patient plan verification, especially in treatments with steep dose gradients and nonuniform dose rates such as VMAT and SRS. Major limitations of the present prototype are the linearity at low dose, which can be solved by optimizing the readout electronics, and the underestimation of output factors with large field sizes. The latter problem is presently not completely understood and will require further investigations.